Arrest sparks boycott of US. (Times Higher Education Supplement, 2001)
Reports on the Electronic Frontier Foundation, a civil liberties organization that aims to protect rights in the digital world, is mounting a campaign to get the United States Department of Justice to drop charges against Russian programmer Dmitry Sklyarov. Arrest of Sklyarov for alleged violation of the Digital Millennium Copyright Act; Sklyarov's creation of software that decrypts Adobe eBook format to bypass copy restrictions.